TFAP2B Haploinsufficiency Impacts Gastrointestinal Function and Leads to Pediatric Intestinal Pseudo-obstruction - Zada, Almira; Kuil, Laura E.; de Graaf, Bianca M.; Kakiailatu, Naomi; Windster, Jonathan D.; Brooks, Alice S.; van Slegtenhorst, Marjon; de Koning, Barbara; Wijnen, René M. H.; Melotte, Veerle; Hofstra, Robert M. W.; Brosens, Erwin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Pediatric Intestinal Pseudo-obstruction (PIPO) is a congenital enteric disorder characterized by severe gastrointestinal (GI) dysmotility, without mechanical obstruction. Although several genes have been described to cause this disease, most patients do not receive a genetic diagnosis. Here, we aim to identify the genetic cause of PIPO in a patient diagnosed with severe intestinal dysmotility shortly after birth. Methods: Whole exome sequencing (WES) was performed in the patient and unaffected parents, in a diagnostic setting. After identification of the potential disease-causing variant, its functional consequences were determined in vitro and in vivo. For this, expression constructs with and without the causing variant, were overexpressed in HEK293 cells. To investigate the role of the candidate gene in GI development and function, a zebrafish model was generated where its expression was disrupted using CRISPR/Cas9 editing. Results: WES analysis identified a de novo heterozygous deletion in TFAP2B (NM_003221.4:c.602-5_606delTCTAGTTCCA), classified as a variant of unknown significance. In vitro studies showed that this deletion affects RNA splicing and results in loss of exon 4, leading to the appearance of a premature stop codon and absence of TFAP2B protein. Disruption of tfap2b in zebrafish led to decreased enteric neuronal numbers and reduced intestinal motility. tfap2b crispants also showed decreased levels of ednrbb mRNA, a downstream target of tfap2b. Conclusion: We showed that TFAP2B haploinsufficiency leads to reduced neuronal numbers and GI dysmotility, suggesting for the first time, that this gene is involved in PIPO pathogenesis.